2015
DOI: 10.1128/mcb.00857-14
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Trapping Proteomics Reveals Targets of the βTrCP2/FBXW11 Ubiquitin Ligase

Abstract: Defining the full complement of substrates for each ubiquitin ligase remains an important challenge. Improvements in mass spectrometry instrumentation and computation and in protein biochemistry methods have resulted in several new methods for ubiquitin ligase substrate identification. Here we used the parallel adapter capture (PAC) proteomics approach to study ␤TrCP2/FBXW11, a substrate adaptor for the SKP1-CUL1-F-box (SCF) E3 ubiquitin ligase complex. The processivity of the ubiquitylation reaction necessita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 74 publications
0
55
0
Order By: Relevance
“…RNAi targeting TrCP1/2 was from Sigma, directed against the sequence GUGGAAUUUGUGGAACAUC, previously reported (32). siGENOME Control siRNA (nontargeting siRNA #5) was used as nontargeting control.…”
Section: Methodsmentioning
confidence: 99%
“…RNAi targeting TrCP1/2 was from Sigma, directed against the sequence GUGGAAUUUGUGGAACAUC, previously reported (32). siGENOME Control siRNA (nontargeting siRNA #5) was used as nontargeting control.…”
Section: Methodsmentioning
confidence: 99%
“…Substrates-While our work was in progress, two additional studies were published on the identification of ␤-TrCP substrates (56,57), utilizing more standard IP-MS and TAP (tandem affinity purification)-MS approaches. Notably, despite the use of widely disparate approaches, many of the same ␤-TrCP interactors were detected among all three studies, significantly expanding the number of high-confidence ␤-TrCP substrates and implicating this already well-studied E3 ligase in several new biological processes.…”
Section: Bioid As a Complementary Approach For The Identification Of E3mentioning
confidence: 99%
“…Furthermore, CompPASS can identify proteins based on a single peptide, increasing the potential for incorrect protein identifications or false-positives [89]. Importantly, PAC-based approaches are unlikely to enrich for monoubiquitylated substrates and substrates that are not fated to be degraded [90]. The PAC–CompPASS approach was recently applied to identify substrates of the FBXW11 ubiquitin ligase adaptor protein [90].…”
Section: Proteomicsmentioning
confidence: 99%
“…Importantly, PAC-based approaches are unlikely to enrich for monoubiquitylated substrates and substrates that are not fated to be degraded [90]. The PAC–CompPASS approach was recently applied to identify substrates of the FBXW11 ubiquitin ligase adaptor protein [90]. This study identified 96 interacting proteins, 23 of which are putative substrates, with 1 independently validated as a substrate [90].…”
Section: Proteomicsmentioning
confidence: 99%